Journal of a voyage to Lisbon. 1793-1794 : a young man’s impressions of the city and its surroundings - Paulino, Maria Clara (CEM – Cultura, Espaço & Memória, 2018)
In November 1793 seventeen-year-old William Withering left England in the company of his father, who suffered from consumption; a few weeks later they arrived in the coast of Lisbon. In Journal of a Voyage to Lisbon. 1793-1794, a manuscript, Withering wrote a daily record of his experiences from the moment he left home, in Birmingham, until his return. In this paper we focus our attention on the 168 pages of the manuscript dedicated to Lisbon and its surroundings, where father and son resided for five months. We examine them against the background of the history and «culture» of travel literature, in particular that between mid-18th and mid-19th cent. Most of our sources are from the universe of travel literature and literary history. We emphasize the singularity of this travel account, which derives from factors such as the reputation of the author’s father (known as the «English Linneus»), and the accessibility to places and objects it facilitated; the Enlightenment travel writing conventions the author followed; and the author’s young age.